An annotated checklist of the aquatic Polyphaga (Coleoptera) of Egypt I. Family Hydraenidae - Salah, Mohamed; Cueto, Juan Antonio Régil; Valladares, Luis F. (Zootaxa, 2014)
Data from previous literature were used to compile a checklist of the Egyptian fauna of Hydraenidae (Coleoptera). The checklist includes data on the type localities, type specimens, descriptors, distributions and previous literature for 15 valid species belonging to 3 genera (Hydraena, Limnebius and Ochthebius). Ochthebius was represented by 13 species, while Hydraena and Limnebius were represented only by a single species for each of them. The present study provides a summary that can serve as the basis for future progress in the knowledge of the Egyptian Hydraenidae.